PERILAKU MENYIMPANG PADA MAHASISWA PENDATANG DI PERUMNAS ALPEN ACEH BARAT - Mardiani Mardiani; Nurkhalis Nurkhalis (Jurnal Society : Pengamat Perubahan Sosial, 2021)
Deviant behavior is all acts that occur in a society that is considered deviant because it violates the rules that have been set and applies in the general public so that these conditions make certain parties participate in correcting deviant behavior. In this case, premarital sexual behavior should not occur in the people of Aceh who already adhere to the Islamic Sharia system, because in Islam premarital sexual behavior is prohibited called adultery. This study is to find out what factors cause deviant behavior in newcomers in the West Aceh National Housing using Social Control Theory. This study uses descriptive qualitative research using data collection techniques using observation, interviews, and documentation. The results of this study can be in the form of premarital sexual behavior, such as being together in a dimly lit place, a non-muhrim handler, kissing, to groping parts that are considered sensitive to a woman's body. This happens because of economic needs, the influence of the environment and mass media, and the inability to absorb the norm.